Attacks and Secure Geographic Routing In Wireless Sensor Networks - Sabri Yassine; Najib El Kamoun (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Due to open network nature of wireless sensor networks make them highly vulnerable to a variety of security attacks and easy target for adversaries, which may capture these nodes, analyze and easily insert fake route information. Wireless sensor network is an emerging, cost effective and unsupervised solution for collecting this information from the physical world and sending this information back to centralized authority for further processing. GRPW (Geographic Routing in connected wireless sensor networks based on Multiple Sinks) is one of the basic routing protocols used for Supporting Mobile Sinks in Wireless Sensor Networks. GRPW, a geographical routing protocol for wireless sensor networks, is based on an architecture partitioned by logical levels, on the other hand based on a multipoint relaying flooding technique to reduce the number of topology broadcast. GRPW-MuS uses periodic HELLO packets to neighbor detection. The wormhole attack can form a serious threat in wireless sensor networks, especially against many wireless sensor networks routing protocols and location-based wireless security systems. Here, a trust model to handle this attack in GRPW is provided called GRPW-MuS-s. Using OMNET++ simulation and the MiXiM framework, results show that GRPW-MuS-s protocol only has very small false positives for wormhole detection during the neighbor discovery process (less than GRPW). The average energy usage at each node for GRPW-MuS-s protocol during the neighbor discovery and route discovery is very low than GRPW-MuS, which is much lower than the available energy at each node. The cost analysis shows that GRPW-MuS-s protocol only needs small memory usage at each node, which is suitable for the sensor network.